Color blind – Investigating customer-based discrimination in European soccer - Quansah, Tommy Kweku; Lang, Markus; Frick, Bernd (Current Issues in Sport Science (CISS), 2023)
This paper tests for the existence and consequences of customer-based racial discrimination in Europe’s five largest professional soccer leagues. Most of the previous studies focusing on European sports, as opposed to North American sports, either used wage models to identify discrimination of e.g., black players or focused on nationality instead of ethnicity or race. This study employs a market test approach to empirically test whether racial preferences affect ticket demand. Using data from the European Big-5 soccer leagues between 2008/09 and 2018/19, the results of our regression models indicate evidence of customer-based discrimination in European soccer, moderated by the idiosyncratic circumstances in each of the five countries and their respective leagues - both in terms of racial as well as nationality-based discrimination. The study fills an important gap in the European sports management literature, as the lack of suitable data has for a long time impeded a thorough investigation of customer-based discrimination and its consequences in European sports – an area well researched in the North American context.